The Influence of E-WOM, E-Trust and E-Service Quality on Purchase Decisions on Shopee E-commerce in Pekalongan City - Hanif Ridho Muttaqin; Muhammad Arifiyanto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This scientific research aims to analyze the influence of E-WOM, E-Trust and E-Service Quality on the decision to purchase goods at E-commerce Shopee in Pekalongan City. This study uses a quantitative approach method, where the population in this study were residents of Pekalongan City with a sample of 100 respondents. The data used is primary data taken from questionnaires to respondents and the analysis tool in this study uses IBM SPSS Statistic 26 software. The results of this study indicate that simultaneously E-WOM, E-Trust and E-Service Quality together have an effect on Purchasing Decisions. Partially, E-WOM has no effect on Purchasing Decisions, E-Trust affects Purchasing Decisions. E-Service Quality affects Purchasing Decisions. This research is expected to be used as a reference for marketplace managers to improve marketing strategies and customer trust in an e-commerce environment.